KAJIAN KONSEP RESILIENT DESIGN UNTUK PENGEMBANGAN KAWASAN WADUK JATIBARANG KOTA SEMARANG - Indriastjario, Indriastjario (MODUL, 2018)
Environmental deterioration which is increasing the area’s vulnerability occured in the Area of Jatibarang Dam in Semarang City. The deterioration is caused by the construction of the Dam. It is worsening the sustainability, disturbing the harmony of the flora & fauna especially the macaca (long-tailed monkey) lost their food and access to the hill , the main area of theirs ; and then due to be a tourism destination area, the development of the surrounding have gradually demolished the landscape and worsening the ecosystem. Therefore, the Dam Area requires an increased capacity to face the deterioration. It needs to be well designed to achieve a state of area that is resistant to deterioration. To form a resilient area, resilient ways are required. The purpose of this research is to find an innovative concept of resilience ways to actualize the sustainability of The Area of Jatibarang Dam in Semarang City through resilience design.The research uses descriptive analysis method based on  the 4 factors of : spatial arrangement, technology innovation, disaster mitigation, and disaster adaptation.The results of the research found the integration of : 1. the enhancement of the adaptive capacity of society (local wisdom of tradition & spiritual heritage), 2. the implementation of orderly spatial management through green architecture and 3. a dynamic and planned urban systems which promote the access for all to actualize a resilient and sustainable area, would be the effective resilient ways to promote the Resilience Design of the Dam Area.